2006
DOI: 10.1186/1477-5956-4-6
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of acidic chaperones, and stress proteins in extreme halophile Halobacterium NRC-1: a comparative proteomic approach to study heat shock response

Abstract: Background: Halobacterium sp. NRC-1 is an extremely halophilic archaeon and has adapted to optimal growth under conditions of extremely high salinity. Its proteome is highly acidic with a median pI of 4.9, a unique characteristic which helps the organism to adapt high saline environment. In the natural growth environment, Halobacterium NRC-1 encounters a number of stressful conditions including high temperature and intense solar radiation, oxidative and cold stress. Heat shock proteins and chaperones play indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 51 publications
(62 reference statements)
0
16
0
2
Order By: Relevance
“…Forty‐four proteins were detected in another study as being differentially expressed in response to changing salt concentrations; 18 of these were identified by MS analysis, among them the stress response protein PspA. Similarly, a 2DE study identified heat shock proteins in Halobacterium . Recently, several large scale quantitative proteome analyses of archaeal organisms have been published, for example, in Halobacterium salinarum .…”
Section: Introductionmentioning
confidence: 99%
“…Forty‐four proteins were detected in another study as being differentially expressed in response to changing salt concentrations; 18 of these were identified by MS analysis, among them the stress response protein PspA. Similarly, a 2DE study identified heat shock proteins in Halobacterium . Recently, several large scale quantitative proteome analyses of archaeal organisms have been published, for example, in Halobacterium salinarum .…”
Section: Introductionmentioning
confidence: 99%
“…Cho and his group [21] studied 2-DE electrophoresis of Halobacterium salinarum by IPG strips and they obtained poor resolution with IPG strips. Shukla [22] studied Halobacterium NRC-I also with the 2-DE IPG strip technique and modified the 2-DE procedure in order to improve resolution and to minimize streaking of proteins in the acidic range. He also noted that the common unmodified 2-DE procedure resulted in horizontal and vertical streaking at the high MW range.…”
Section: Resultsmentioning
confidence: 99%
“…Ribosomal protein genes responding to low-temperature stress are common in plants, such as rps27ae, rphs6, kog3491, and L23A (Shukla 2006;Lang 2005;McIntosh and Bonham-Smith 2005). In soybean, gmrps13, gmrps6, and gmrps37 have been reported to enhance translation under low-temperature conditions, and may have different functions in metabolic processes (Kim et al 2004).…”
Section: Analysis Of Sol34mentioning
confidence: 97%